Spatial Spillover and Interaction Between High-Tech Industrial Agglomeration and Urban Ecological Efficiency - Wang, Mengxin; Li, Yanling; Liao, Gaoke (Frontiers in Environmental Science, 2022)
The spatial relationship between high-tech industrial agglomeration and urban eco-logical efficiency has been widely concerned. This study empirically analyzed the bidirectional influence relationship between high-tech industrial agglomeration and urban ecological efficiency and its spatial spillover effect by constructing a spatial simultaneous equation model, and based on the classification of urban resource endowment, this paper studies the heterogeneity of spatial spillover effects between high-tech industrial agglomeration and urban ecological efficiency based on the sample data of 285 cities in China from 2004 to 2017. The empirical results reveal the following: first, there is a two-way promoting effect between high-tech industrial agglomeration and urban ecological efficiency; Second, there is a significant spatial spillover effect of urban ecological efficiency, that is, the urban ecological efficiency in this region is significantly positively correlated with the urban ecological efficiency in neighboring regions; Third, there is a significant difference in the regional interaction between high-tech industry agglomeration and urban eco-efficiency, that is, the urban eco-efficiency in the neighboring areas has a significant negative impact on the regional high-tech industry agglomeration, while the high-tech industry agglomeration in the neighboring areas has a negative but not significant impact on the regional urban eco-efficiency; Fourth, the spatial interaction spillover effects between high-tech industrial agglomeration and urban ecological efficiency are heterogeneous in terms of regional resources, and the results of regional interaction and spatial spillover effects are better in the sample study.